Effect of season on efficacy of estrus synchronization protocols and plasma progesterone profile in anoestrus crossbred cows - Borkhatariya, D N; Panchal, M T; Dhami, A J; Hadiya, K K; Mungad, K S; Sarvaiya, N P (Indian Journal of Dairy Science, 2017)
A study was carried out with an aim to evaluate comparative estrus response, fertility and plasma progesterone profile of three estrus synchronization protocols during winter (n=40) and summer (n=43) seasons in > 90 days postpartum true anoestrus crossbred cows including anoestrus controls (n=10) in both the seasons. The selected animals were randomly divided into four groups and placed under three different estrus synchronization protocols, i.e., Ovsynch, Heatsynch and Triu-B, and a control. In winter season, the estrus induction response was 100 per cent in each group, while in summer season the estrus response was 80.00, 90.00 and 80.00 per cent with Ovsynch, Heatsynch and Triu-B protocols, respectively. The conception rates in winter season at induced estrus were 45.45, 27.27 and 36.36 per cent and overall of 3 cycles 72.72, 45.45 and 63.64 per cent, while in summer season the corresponding conception rates for three protocols were 30.00, 20.00 and 20.00 per cent, and 60.00, 40.00 and 50.00 per cent, respectively. The estrus and conception rates were better with all three protocols during winter than summer season. The results with Heatsynch protocol were however inferior in both the seasons. The mean plasma progesterone profile on day ‘0’ was the lowest or basal (<0.50 ng/ml), while on day ‘7’ the levels were 3.32±0.48, 2.82±0.96, 4.34±1.60 ng/ml in winter and 3.40±0.68, 3.09±0.59, 3.14±0.52 ng/ml in summer. Further, on day ‘9’ the levels were dropped to <0.74±0.12 ng/ml in winter and< 0.52±0.11 ng/ml in summer. On day 21 post-AI the levels were 3.11±0.74, 2.69±2.03, 3.06±2.59 ng/ml in winter and 2.26±0.77, 2.95±0.69, 1.53±0.67 ng/ml in summer season for three protocols, suggesting apparent or significant effect of seasons. It was concluded that in winter season all three protocols, and in summer season Ovsynch and Triu-B protocols may be used to ameliorate anoestrus in crossbred cows at field level as they showed good estrus induction response and conception rates in respective seasons.